Mapping the Multi-Organ miRNA-mRNA Regulatory Network in LPS-Mediated Endotoxemic Mice: Exploring the Shared Underlying Key Genes and Mechanisms - Zhang, Cong; Liao, Ying; Liu, Zhihao; Zeng, Lijin; Peng, Zhihua; Liao, Jinli; Yang, Zhen (Frontiers in Molecular Biosciences, 2020)
Background: To this day, the molecular mechanism of endotoxin-induced multi-organ failure has not been completely clarified. This study aimed to construct miRNA-mRNA regulatory network and identify main pathways and key genes in multi-organ of LPS-mediated endotoxemic mice. Methods: Public datasets from 6 mRNA and 3 miRNA microarray datasets were downloaded from the GEO website to screen final differentially expressed genes (FDEGs) and hub genes in heart, lung, liver and kidney of LPS-mediated endotoxemic mice. Functional and pathway enrichment analysis of FDEGs was used to identify the main pathways in multi-organ damage of LPS-treated mice. Finally, hub genes of each organ were intersected to obtain the key genes of multi-organ. Results: Firstly,158, 358, 299 and 91 FDEGs were identified in the heart, lung, liver and kidney, respectively. Then the pathway enrichment analysis of FDEGs showed that TNF signaling pathway, Toll-like receptor signaling pathway and some viral infection related pathways (influenza A, measles and herpes simplex) were main pathways in multi-organ damage of LPS-mediated endotoxemic mice. Moreover, miRNA-mRNA or PPI regulatory networks were constructed based on FDEGs. According to these networks, 31, 34, 34, and 31 hub genes were identified in heart, lung, liver and kidney, respectively. Among them, 9 key genes (Cd274, Cxcl1, Cxcl9, Icam1, Ifit2, Isg15, Stat1, Tlr2 and Usp18) were enriched in Toll-like receptor signaling pathway and chemokine signaling pathway. Finally, 7 potential drugs were predicted based on these key genes. Conclusion: The shared underlying molecular pathways in endotoxin-induced multi-organ damage that have been identified include Toll-like receptor signaling pathway and TNF signaling pathway. Besides, 9 key genes (Cd274, Cxcl1, Cxcl9, Icam1, Ifit2, Isg15, Stat1, Tlr2 and Usp18) and 7 potential drugs were identified. Our data provide a new sight and potential target for future therapy in endotoxemia-induced multi-organ failure.